Accelerating Seed Germination and Juvenile Growth of Sorghum (Sorghum bicolor L. Moench) to Manage Climate Variability through Hydro-Priming - Dembélé, Siaka; Zougmoré, Robert B.; Coulibaly, Adama; Lamers, John P.A.; Tetteh, Jonathan P. (MDPI, 2021)
Agriculture in Mali, a country in Sahelian West Africa, strongly depends on rainfall and concurrently has a low adaptive capacity, making it consequently one of the most vulnerable regions to climate change worldwide. Since early-season drought limits crop germination, and hence growth, ultimately yield during rain-fed depending on production is commonly experienced nowadays in Mali. Germination and establishment of key crops such as the staple sorghum could be improved by seed priming. The effects of hydro-priming with different water sources (e.g., distilled, tap, rain, river, well water) were evaluated respectively for three priming time durations in tepid e.g., at 25 °C (4, 8, and 12 h) and by hot water at 70 °C (in contrast to 10, 20, and 30 min.) in 2014 and 2015. Seed germination and seedling development of nine sorghum genotypes were monitored. Compared to non-primed seed treatments, hydro-priming significantly [p = 0.01] improved final germination percentage, germination rate index, total seedling length, root length, root vigor index, shoot length, and seedling dry weight. The priming with water from wells and rivers resulted in significant higher seed germination (85%) and seedling development, compared to the three other sources of water. Seed germination rate, uniformity, and speed were enhanced by hydro-priming also. It is argued that hydro-priming is a safe and simple method that effectively improve seed germination and seedling development of sorghum. If used in crop fields, the above most promising genotypes may contribute to managing early season drought and avoid failure of seed germination and crop failure in high climate variability contexts